Numerical simulation of closure performance for neo-aortic valve for arterial switch operation. Issue 2 (December 2016) - Gu, Zhaoyong; Pan, Youlian; Qiao, Aike; Hu, Xingjian; Dong, Nianguo; Li, Xiaofeng; Liu, Yinglong; Shang, Deguang
Abstract Background Modeling neo-aortic valve for arterial switch surgical planning to simulate the neo-aortic valve closure performance. Methods We created five geometrical models of neo-aortic valve, namely model A, model B, model C, model D and model E with different size of sinotubular junction or sinus. The nodes at the ends of aorta and left ventricle duct fixed all the degrees of freedom. Transvalvular pressure of normal diastolic blood pressure of 54 mmHg was applied on the neo-aortic valve cusps. The neo-aortic valve closure performance was investigated by the parameters, such as stress of neo-aortic root, variation of neo-aortic valve ring as well as aortic valve cusps contact force in the cardiac diastole. Results The maximum stress of the five neo-aortic valves were 96.29, 98.34, 96.28, 98.26, and 90.60 kPa, respectively. Compared among five neo-aortic valve, aortic valve cusps contact forces were changed by 43.33, −10.00% enlarging or narrowing the sinotubular junction by 20% respectively based on the reference model A. The cusps contact forces were changed by 6.67, −23.33% with sinus diameter varying 1.2 times and 0.8 times respectively. Conclusions Comparing with stress of healthy adult subjects, the neo-aortic valve of infant creates lower stress. It is evident that enlarging or narrowing the sinotubular junction within a range of 20% can increase or decrease the maximum stress and aortic valve cusps contact force of neo-aortic valve.